2021
DOI: 10.1136/bmjopen-2020-045276
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the risk of drug–drug interactions in psychiatric hospitals: a retrospective longitudinal pharmacovigilance study

Abstract: ObjectivesThe aim was to use routine data available at a patient’s admission to the hospital to predict polypharmacy and drug–drug interactions (DDI) and to evaluate the prediction performance with regard to its usefulness to support the efficient management of benefits and risks of drug prescriptions.DesignRetrospective, longitudinal study.SettingWe used data from a large multicentred pharmacovigilance project carried out in eight psychiatric hospitals in Hesse, Germany.ParticipantsInpatient episodes consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
5
1
Order By: Relevance
“…Although other studies have shown that the number of diagnoses increases with the number of pDDIs, this may not hold for psychiatric patients in hospital settings 22. Some studies have shown that age is a significant risk factor for pDDIs,2 6 12 while some have not confirmed this association 23 24. Our study showed that age is a protective factor, which can be explained by greater care and more detailed analysis of therapy in elderly patients because they usually have more comorbidities, resulting in more drugs and an increased risk of potential interactions between them 21.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Although other studies have shown that the number of diagnoses increases with the number of pDDIs, this may not hold for psychiatric patients in hospital settings 22. Some studies have shown that age is a significant risk factor for pDDIs,2 6 12 while some have not confirmed this association 23 24. Our study showed that age is a protective factor, which can be explained by greater care and more detailed analysis of therapy in elderly patients because they usually have more comorbidities, resulting in more drugs and an increased risk of potential interactions between them 21.…”
Section: Discussioncontrasting
confidence: 50%
“…The risks from DDIs are substantially increased in patients with more comorbidities, and the same was shown by the study of Wolff et al 12. With increased CRP values, antibiotic administration was more frequent, increasing the risk of pDDIs.…”
Section: Discussionmentioning
confidence: 59%
“…a main diagnosis of F32 � or F33 � , ICD-10. Previous publications from this research project can be found in the reference list [10,12,14,[23][24][25][26].…”
Section: Study Samplementioning
confidence: 99%
“…A possible way to mitigate resource constraints in hospitals is the use of modern technologies to make services more cost-effective 4 . For instance, the increasing availability of data allows to support medical decision making in hospitals with information derived from machine learning algorithms 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%